Natural Resource Management through land developmental process with heavy farm machinery - Ranade, Deepak Hari (Indian Farming, 2015)
Various soil and water conservation measures have been created in different watersheds of the ORP, Indore region utilizing heavy machines. The creation of water bodies, straightening of the nala, drainage line treatment brought about visible changes and helped in managing the natural resources in the region. The use of heavy machines not only completed work on time but also saved the expenditure which would have been otherwise almost double if the manual force was utilized. Therefore it can be pointed out that besides man, money, materials, machines also play a very significant role in natural resource conservation programmes.